Analisis Laju Pertumbuhan Karang Acropora sp. Pada Transplantasi Di Pantai Pandawa dan Pulau Serangan, Bali - Pratiwi, Diah Eka; Watiniasih, Ni Luh Watiniasih; Ayu Pratiwi, Made Ayu Pratiwi (Current Trends in Aquatic Science; Vol 6 No 1 (2023), 2023)
This study aims to determine the growth rate of Acropora corals with the relationship of water parameters at Pandawa Beach and Serangan Island. Coral growth rate in this study was measured by the increase in coral width, fragment width, height, and total number of coral fragments. The results showed that the growth of Acropora sp. corals in Serangan Island experienced a faster increase with Pandawa Beach. Based on the correlation results that the water quality at Pandawa Beach and Serangan Island has a correlation relationship to the growth rate of Acropora sp. corals. water quality parameters at Pandawa Beach and Serangan Island are in accordance with the quality standards of seawater for marine biota. The water quality parameters of Pandawa Beach and Serangan Island are in accordance with the quality standards set by the Decree of the Minister of Environment No. 51 of 2004 concerning Seawater Quality Standards for marine biota. Based on the results of water quality research for 3 repetitions and taken every 2 weeks, the characteristics of water quality values at Pandawa Beach are temperature values of 26.2 - 28.5, brightness of 100%, depth of 0.8-1.5m, salinity of 32-34‰, current speed of 0.1-0.2m/s, pH of 7.7-7.9, Do of 6-7.6. The characteristic values of water quality in Serangan Island are temperature of 27.7-30.1, brightness of 50-75%, depth of 2.4-2.8m, salinity of 31-33‰, current speed of 0.2-0.3m/s, pH of 7.7-7.9, Do of 4.6-7.6.